MORFOMETRI KERANG TAHU Meretrix meretrix Linnaeus, 1758 DI PASAR RAKYAT MAKASSAR - A. Gita Maulidyah Indraswari; Magdalena Litaay; Eddy Soekendarsi (BERITA BIOLOGI, 2014)
White shells Meretrix meretrix is one of the bivalves that are often sold in local markets of Makassar. Meretrix meretrix is one type of shellfishes that is favoured by the people so that they are continuedly being taken from their habitat without considering the feasibility of the capture. This research was aimed to determine the correlation between shell length, shell width, shell thickness, and total weight of the meat as well as assessing the size of a decent catch of M. meretrix in Makassar. Morphometric relationship between the length, width and thickness of the shell and total weight of the meat was analyzed using regression analysis.The results showed that the length and width of the shell and the length and total weight had strong positive correlation (0.81 = r = 0.96 and 0.81 = r = 0,92 repectively).The lenght and thickness of shell was moderately correlated (0.57 = r = 0.76), while the length and weight of the meat showed weak correlation (0.02 = r = 0.47). Size of M. meretrix sold in TPI Rajawali, Sentral market and Tanjung market ranged between 2.00 – 6.99 cm and has fulfilled the catching standard, which is > 4 cm.